2012
DOI: 10.1037/a0028610
|View full text |Cite
|
Sign up to set email alerts
|

When and how is job embeddedness predictive of turnover? A meta-analytic investigation.

Abstract: The present meta-analytic study introduces an overall model of the relationships between job embeddedness and turnover outcomes. Drawing on 65 independent samples (N = 42,907), we found that on-the-job and off-the-job embeddedness negatively related to turnover intentions and actual turnover, after controlling for job satisfaction, affective commitment, and job alternatives. In addition, the negative relationships between on-the-job embeddedness (off-the-job embeddedness) and turnover criteria were stronger in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
377
3
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(440 citation statements)
references
References 90 publications
23
377
3
9
Order By: Relevance
“…beyond being involved in organizational activities that increase an individual's investment in their job (Jiang et al, 2012;. People who are more strongly connected to others tend to be resistant to particular shocks that might lead others to start quitting processes ).…”
Section: Voluntary Turnovermentioning
confidence: 99%
See 1 more Smart Citation
“…beyond being involved in organizational activities that increase an individual's investment in their job (Jiang et al, 2012;. People who are more strongly connected to others tend to be resistant to particular shocks that might lead others to start quitting processes ).…”
Section: Voluntary Turnovermentioning
confidence: 99%
“…This broad ranging theory postulates that an employee's embeddedness in the workplace, that is, the extent to which they are connected to other individuals or groups, makes employees less likely to leave (Felps, Mitchell, Hekman, Lee, Holtom, & Harman, 2009;Jiang, Liu, McKay, Lee, & Mitchell, 2012;Lee, Mitchell, Sablynski, Burton, & Holtom, 2004;Mitchell, Holtom, Lee, Sablynski, & Erez, 2001). The theory of job embeddedness examines how turnover is related to the number of coworkers that an individual interacts with (links), the extent to which a job fits an individual's life (fit), and what they would be giving up by leaving a job (sacrifice) ).…”
Section: Introductionmentioning
confidence: 99%
“…Simply put, we do not yet know what the key forces are in a given setting, organization, industry, or profession. For example, different profiles of causal indicators may hold across private and public organizations' employees (Jiang et al 2012) versus radiologists and surgeons (Pratt et al 2006) versus humanities and life science professors. Further, these forces may not operate in a simple linear fashion.…”
Section: What Is the Empirical Structure Of Job Embeddedness?mentioning
confidence: 99%
“…Jiang (2012) analysis found that the negative correlation between organizational embeddedness and turnover intention was more significant in female dominated organizations and public institutions. The influence of community embeddedness on turnover intention is stronger in collectivism culture [1]. The study of Holtom (2013) found that the predictive power of job embeddedness on turnover enhanced with the increase of working years [2].…”
Section: A Organizational Embeddedness and Job Performancementioning
confidence: 97%